Computational study of the a1A-adrenoceptor and its ligands - Kinsella, Gemma (Trinity College (Dublin, Ireland). School of Chemistry, 2005)
Adrenoceptors belong to the 'super-family' of seven transmembrane domain receptors known as G protein coupled receptors (GPCRs), which produce their effects through coupling with G proteins. Nine different subtypes of adrenoceptors (ARs) have been identified based on the results of pharmacological and molecular cloning studies, of which the α1-A R subtypes are associated with the condition Benign Prostatic Hyperplasia (BPH). BPH effects 50 % of men over the age of 50 and due to increased life expectancy the proportion of men suffering from BPH will increase significantly over the coming years. Prostatic smooth muscle contraction occurs predominantly, if not exclusively, via the α1A-AR subtype and antagonists selective for this particular receptor might be most useful in alleviating the urological symptoms of BPH which include increased frequency in urination, nocturia, a poor urine stream and hesitancy or delay in starting flow.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin